2015
DOI: 10.3389/fmed.2015.00073
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Risk Factors, Interventions, and Comorbidity in Patients with Non-Specific Low Back Pain in Primary Care: Need for Comprehensive and Patient-Centered Care

Abstract: Non-specific low back pain (LBP) affects many people and has major socio-economic consequences. Traditional therapeutic strategies, mainly focused on biomechanical factors, have had moderate and short-term impact. Certain psychosocial factors have been linked to poor prognosis of LBP and they are increasingly considered as promising targets for management of LBP. Primary health care providers (HCPs) are involved in most of the management of people with LBP and they are skilled in providing comprehensive care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 151 publications
(169 reference statements)
1
43
0
6
Order By: Relevance
“…However, predictive quantitative analysis of future pain illustrated that lifestyle factors, for example, demanding physical work, gender and smoking outweighed medical care factors, such as case history, therapy form, iatrogenic factors and type of insurance. Although the frequent use of prescribed pain medications in combination can become undetected medication abuse, a topic that should receive more attention, it is important to note that sociodemographic and lifestyle factors have a huge influence on the medical history of patients 14. Research is beginning to uncover that declared orange flag factors (e.g., substance abuse, gender) are of greater importance than suggested in the current flag catalog and should be respected by health care providers 9,48.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, predictive quantitative analysis of future pain illustrated that lifestyle factors, for example, demanding physical work, gender and smoking outweighed medical care factors, such as case history, therapy form, iatrogenic factors and type of insurance. Although the frequent use of prescribed pain medications in combination can become undetected medication abuse, a topic that should receive more attention, it is important to note that sociodemographic and lifestyle factors have a huge influence on the medical history of patients 14. Research is beginning to uncover that declared orange flag factors (e.g., substance abuse, gender) are of greater importance than suggested in the current flag catalog and should be respected by health care providers 9,48.…”
Section: Discussionmentioning
confidence: 99%
“…This helps practitioners to distinguish between individual perception and objective features to then create specific interventions targeted at modifiable risks. In the past, the following factors have been proposed in different flag domains:9 sociodemographic factors such as age, gender, socioeconomic status and cultural conditions,4,10behavioral factors such as fear avoidance, endurance, catastrophizing, anxiety and depression,1015 andoccupational factors such as employment status/dissatisfaction/expectations/body posture and social support (SS) at the workplace 14,16–18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VISAT study emphasises the role of different categories of occupational factors on focused types of LPB and the need to take into consideration the onset time of CLBP. When LBP progresses towards a chronic form, with daily pain and a need for drugs, occupational biomechanical and psycho-organisational factors have to be considered to manage LBP, as suggested in several guidelines53 54 and in a recent review 55…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest the presence of preexisting functional and morphologic risk factors for the development of chronic back pain, although the preexistence of these factors remains to be proven. It should be noted that earlier clinical studies have identified a long list of risks for chronic pain, such as demographics, affective states, lifestyle, comorbidities, and others (Mayer and Bushnell 2009), yet collectively such parameters account for a relatively small amount of variance for chronic pain (10% to 20%; Hasenbring et al 2012;Ramond-Roquin et al 2015). In contrast, the brain's anatomic and functional properties predict development of chronic pain at 80% to 100% accuracy.…”
Section: The Corticolimbic System As a Predictor And Determinant Of Cmentioning
confidence: 99%